1995
DOI: 10.1037/0022-3514.68.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Sexism and racism: Old-fashioned and modern prejudices.

Abstract: Prejudice and discrimination against women has become increasingly subtle and covert (N. V. Benokraitis & J. R. Feagin, 1986). Unlike research on racism, little research about prejudice and discrimination against women has explicitly examined beliefs underlying this more modern form of sexism. Support was found for a distinction between old-fashioned and modern beliefs about women similar to results that have been presented for racism (J. B. McConahay, 1986;D. O. Sears, 1988). The former is characterized by en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
1,180
4
48

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,180 publications
(1,285 citation statements)
references
References 54 publications
(79 reference statements)
29
1,180
4
48
Order By: Relevance
“…Whereas Eagly and Mladinic found the AWS to be uncorrelated with general attitudes toward women (as measured by the same semantic differential scales used in Studies 4-6), we have demonstrated that the ASI subscales are related to both attitudes toward and stereotypes about women. Swim et al?s (1995) Modem Sexism and Tougas et al?s (1995) Neo-Sexism scales measure issues similar to those of the AWS, but in a more subtle manner that reflects the greater egalitarianism toward women that has come about in recent decades. Our finding that HS correlates strongly with the Modem Sexism scale, whereas BS does not, supports the notion that the beliefs the Modern Sexism scale taps do reflect hostility toward women.…”
Section: The Asi and Other Measures Of Sexismmentioning
confidence: 99%
“…Whereas Eagly and Mladinic found the AWS to be uncorrelated with general attitudes toward women (as measured by the same semantic differential scales used in Studies 4-6), we have demonstrated that the ASI subscales are related to both attitudes toward and stereotypes about women. Swim et al?s (1995) Modem Sexism and Tougas et al?s (1995) Neo-Sexism scales measure issues similar to those of the AWS, but in a more subtle manner that reflects the greater egalitarianism toward women that has come about in recent decades. Our finding that HS correlates strongly with the Modem Sexism scale, whereas BS does not, supports the notion that the beliefs the Modern Sexism scale taps do reflect hostility toward women.…”
Section: The Asi and Other Measures Of Sexismmentioning
confidence: 99%
“…All items described rights that had historically been statutorily denied to trans persons in the UK (See Table 4 for items). The final three measures were standardized prejudice scales; the short form of Herek's (1984Herek's ( , 1993 Attitudes to Lesbians and Gay men scale (ATLG), Swim, Aikin, Hall and Hunter's (1995) Modern Sexism scale (MS) and Altemeyer's (1996) Right-Wing Authoritarianism scale (RWA). ATLG included five items about gay men and five items about lesbians, MS included eight items, and RWA included thirty.…”
Section: Methodsmentioning
confidence: 99%
“…Men and women differ in their beliefs about the persistence and origins of gender inequality in society ostensibly due to differences in personal experiences with gender discrimination (Manza and Brooks 1998). On average, men are more likely to attribute gender-based inequality to individual women and their personal choices, whereas women are more likely to attribute inequality to systematic discrimination against women (Swim et al 1995). These beliefs about the origins of gender-based inequality-often referred to as modern sexism-shape policy attitudes.…”
Section: Origins Of Gender Gaps In Issue Attitudesmentioning
confidence: 99%